Amyotrophic Lateral Sclerosis Genetic Access Program: Paving the Way for Genetic Characterization of ALS in the Clinic. (October 2021) - Roggenbuck, Jennifer; Rich, Kelly A.; Vicini, Leah; Palettas, Marilly; Schroeder, Joceyln; Zaleski, Christina; Lincoln, Tara; Drury, Luke; Glass, Jonathan D.
Abstract : Objective: To report the frequency of amyotrophic lateral sclerosis (ALS) genetic variants in a nationwide cohort of clinic-based patients with ALS with a family history of ALS (fALS), dementia (dALS), or both ALS and dementia (fALS/dALS). Methods: A multicenter, prospective cohort of 573 patients with fALS, dALS, or fALS/dALS, underwent genetic testing in the ALS Genetic Access Program (ALS GAP), a clinical program for clinics of the Northeast ALS Consortium. Patients with dALS underwent C9orf72 hexanucleotide repeat expansion (HRE) testing; those with fALS or fALS/dALS underwent C9orf72 HRE testing, followed by sequencing of SOD1, FUS, TARDBP, TBK1, and VCP . Results: A pathogenic (P) or likely pathogenic (LP) variant was identified in 171/573 (30%) of program participants. About half of patients with fALS or fALS/dALS (138/301, 45.8%) had either a C9orf72 HRE or a P or LP variant identified in SOD1, FUS, TARDBP, TBK1, or VCP . The use of a targeted, 5-gene sequencing panel resulted in far fewer uncertain test outcomes in familial cases compared with larger panels used in other in clinic-based cohorts. Among dALS cases 11.8% (32/270) were found to have the C9orf72 HRE. Patients of non-Caucasian geoancestry were less likely to test positive for the C9orf72 HRE, but were more likely to test positive on panel testing, compared with those of Caucasian ancestry. Conclusions: The ALS GAP program provided a genetic diagnosis to ∼1 in 3 participants and may serve as a model for clinical genetic testing in ALS.